Physico-chemical Characteristics of Jelly Drink with Variation of Red Dragon Fruit Peel (Hylocereus polyrhizus) and Additional Sappan Wood (Caesalpinia sappan) - Indriani, Osa Desvy; Khairi, Amalya Nurul (Journal of Agri-Food Science and Technology, 2023)
Red dragon fruit peel can be developed into a jelly drink because it naturally contains pectin which can be used as a thickening agent. Sappan wood contains bioactive substances including antioxidants of 15.69 ppm, anthocyanin 2.43%, and brazilin which can increase the red color in jelly drinks. This study contributes to determining the physicochemical characteristics of the red dragon fruit peel jelly drink with the addition of sappan wood. This study consisted of three formulations and a control. The concentrations of red dragon fruit peel and sappan wood were F1=1.5:0.5, F2=1.7:0.3, F3=1.9:0.1, and control (F4=2 :0). The product evaluation consists of pH, gel strength, viscosity, crude fiber, and moisture content. This study showed that the physical properties of jelly drink had a pH value between 6.49-6.67, a gel strength between 0.20-0.22, and a viscosity between 372-583 mPa.s. The chemical properties of jelly drinks have 1.29-2.13% crude fiber and 71.27-76.69% moisture content. This study showed that the higher the red dragon fruit peel concentration and the lower the sappan wood used, the higher the gel strength, viscosity, and crude fiber content, and lowered the pH value and moisture content.